2023
DOI: 10.3390/ijms24076285
|View full text |Cite
|
Sign up to set email alerts
|

6-Gingerol Ameliorates Hepatic Steatosis, Inflammation and Oxidative Stress in High-Fat Diet-Fed Mice through Activating LKB1/AMPK Signaling

Abstract: 6-Gingerol, one of the major pharmacologically active ingredients extracted from ginger, has been reported experimentally to exert hepatic protection in non-alcoholic fatty liver disease (NAFLD). However, the molecular mechanism remains largely elusive. RNA sequencing indicated the significant involvement of the AMPK signaling pathway in 6-gingerol-induced alleviation of NAFLD in vivo. Given the significance of the LKB1/AMPK pathway in metabolic homeostasis, this study aims to investigate its role in 6-gingero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Research indicates that increased hepatic lipogenesis in NAFLD patients is associated with activating SREBP‐1c, a transcription factor that plays a major role in regulating lipogenic proteins such as FAS. Overexpression of SREBP‐1c has been shown to induce hepatocyte steatosis, and AMPK is responsible for controlling SREBP‐1c activity in the liver (Fang et al., 2022 ; Kawamura et al., 2022 ; Liu et al., 2023 ). PPARα, a ligand activator, controls various aspects of lipid catabolism and serves as a major regulator of lipid oxidation in the liver, thus reducing hepatic lipid levels (Jia et al., 2013 ; Rakhshandehroo et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that increased hepatic lipogenesis in NAFLD patients is associated with activating SREBP‐1c, a transcription factor that plays a major role in regulating lipogenic proteins such as FAS. Overexpression of SREBP‐1c has been shown to induce hepatocyte steatosis, and AMPK is responsible for controlling SREBP‐1c activity in the liver (Fang et al., 2022 ; Kawamura et al., 2022 ; Liu et al., 2023 ). PPARα, a ligand activator, controls various aspects of lipid catabolism and serves as a major regulator of lipid oxidation in the liver, thus reducing hepatic lipid levels (Jia et al., 2013 ; Rakhshandehroo et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…to induce hepatocyte steatosis, and AMPK is responsible for controlling SREBP-1c activity in the liver (Fang et al, 2022;Kawamura et al, 2022;Liu et al, 2023). PPARα, a ligand activator, controls various aspects of lipid catabolism and serves as a major regulator of lipid oxidation in the liver, thus reducing hepatic lipid levels (Jia et al, 2013;Rakhshandehroo et al, 2010).…”
Section: Effect Of Hp On Ampk Signaling Pathway In Livermentioning
confidence: 99%
“…6,7 In addition, 6-G was reported to ameliorate hepatic steatosis by activating the LKB1/AMPK pathway. 8 6-Gingerol treatment also significantly reduced the levels of triglyceride, cholesterol, glucose, insulin resistance, and leptin while increasing the levels of liver antioxidant enzymes and adiponectin. 9,10 Although 6-G has been shown to have antioxidant and antiobesity properties in numerous studies, its potential to reduce lipid accumulation in pancreatic tissues has not been investigated.…”
mentioning
confidence: 87%
“…Previous studies have proven that 6-gingerol (6-G), the active compound of ginger, has activity as an antioxidant, antiobesity, antidiabetic, antinausea, and antiemetic triggered by chemotherapy 6,7 . In addition, 6-G was reported to ameliorate hepatic steatosis by activating the LKB1/AMPK pathway 8 . 6-Gingerol treatment also significantly reduced the levels of triglyceride, cholesterol, glucose, insulin resistance, and leptin while increasing the levels of liver antioxidant enzymes and adiponectin 9,10 …”
mentioning
confidence: 99%
“…6-Gingerol ( C4 ), an alkylated phenol from ginger, has various pharmacological effects, including a reduction of inflammatory factors and oxidative stress, an improvement of lipid profile and a reduction of glycemia [ 80 , 81 ]. Several recent studies have shown that the lipid-lowering and antidiabetic effects of 6-gingerol are mediated by PPAR receptors [ 82 , 83 ], notably the PPAR-γ receptor, allowing it to induce hypoglycemic and anti-hyperglycemic effects via a decrease in the expression of SREBP-1c and ChREBP [ 84 , 85 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 99%